Current and Future Spatial Assessment of Biological Control as a Mechanism to Reduce Economic Losses and Carbon Emissions: The Case of Solanum Sisymbriifolium in Africa - Vergara-Egert, P; Alaniz-Baeza, A; Carvajal-Leon, M (John Wiley and Sons Ltd, 2020)
BACKGROUND: Solanum sisymbriifolium is a native plant of South America introduced into Africa, which has detrimental effects on crop yields, and on the environment due to weed control treatment by burning. In South America, S. sisymbriifolium is naturally controlled by the beetle Gratiana spadicea, making this a potential option for its control in Africa. Here, we aim to generate current and future scenarios for the introduction of G. spadicea as a biocontrol agent in Africa, analysing: (i) current and future effective biocontrol areas; (ii) potentially avoided economic losses (AEL), and chemical control costs and savings; and (iii) avoided carbon emissions (ACE) associated with the non-burning of crop fields. We combine species distribution models (SDM) with land cover maps to estimate current and future effective biocontrol considering Representative Concentration Pathways (RCP) 4.5 and 8.5 climate change scenarios. We then estimate AEL and ACE using biocontrol, and chemical control costs and savings. RESULTS: The effective biocontrol area reached 392 405 km2 in 18 countries, representing 40% of potentially affected croplands. Climate change induced a decrease in affected croplands and effective biocontrol. The estimated AEL reached US$45 447.2 ± 5617.3 billion distributed across 16 countries, while the estimated chemical control costs and savings reached US$1988.5 billion and 1411.8 billion, respectively. Potential ACE reached 36.3 ± 5.4 Tg. CONCLUSIONS: Our study provides evidence for the potential benefits of biological controllers on economic losses and carbon emissions, which can be incorporated into sustainable development in low-income countries. © 2020 Society of Chemical Industry